2006
DOI: 10.1897/05-638r.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds associated with testosterone depressions in fish exposed to bleached kraft pulp and paper mill chemical recovery condensates

Abstract: In previous experiments, bleached kraft chemical recovery condensates generated during softwood pulp production have been identified as a primary source of substances causing testosterone depressions in mummichog (Fundulus heteroclitus). Recent toxicity identification evaluations have encountered inconsistencies in the potential of condensates and fractions to reduce steroid concentrations between three repeated exposures. To assess the sources of these inconsistencies, temporal assessments of condensate extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Chem. A series of potential candidate compounds responsible for steroid depression were recently identified by GC-MS detection [37], including diterpenoids, sesquiterpenoids, and stilbenes, and semiquantitative concentrations related to different mill extracts support the hypothesis that similar chemicals may produce hormonal effects in spite of the different wood furnished. New research has increased the potential sources of variability in in vitro assays further, indicating that stress protein hsp90 function is critical for ER signaling and estrogenic endocrine disruption in experiments evaluating rainbow trout hepatocyte VTG production [34].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Chem. A series of potential candidate compounds responsible for steroid depression were recently identified by GC-MS detection [37], including diterpenoids, sesquiterpenoids, and stilbenes, and semiquantitative concentrations related to different mill extracts support the hypothesis that similar chemicals may produce hormonal effects in spite of the different wood furnished. New research has increased the potential sources of variability in in vitro assays further, indicating that stress protein hsp90 function is critical for ER signaling and estrogenic endocrine disruption in experiments evaluating rainbow trout hepatocyte VTG production [34].…”
Section: Discussionmentioning
confidence: 90%
“…That research demonstrated a consistent steroid depression observed as a significant reduction in circulating testosterone in both sexes using both in vivo and in vitro assays (gonad production protocol). A series of potential candidate compounds responsible for steroid depression were recently identified by GC-MS detection [37], including diterpenoids, sesquiterpenoids, and stilbenes, and semiquantitative concentrations related to different mill extracts support the hypothesis that similar chemicals may produce hormonal effects in spite of the different wood furnished. Despite the similarities with this pulp mill effluent solid-phase extraction protocol, samples extracted in our experiment correspond to a final postbleaching process effluent and focus on the polar compounds, different to the condensates from evaporators in the chemical recovery process, which focus on the nonpolar fraction.…”
Section: Discussionmentioning
confidence: 90%
“…The alkaline stream (67% of the final effluent flow) decreased egg production and caused VTG induction and ovipositor development in males. Condensates at this mill also contained chemicals associated with the steroid depressions in mummichog [98]. Additional studies are required to further delineate these sources.…”
Section: Source and Nature Of Suspected Causative Agentsmentioning
confidence: 99%
“…Studies in the field (LeBlanc and Bain, 1997), artificial streams (Dubé and MacLatchy, 2000) and laboratory Hewitt et al, 2002;Belknap et al, 2006;Shaughnessy et al, 2007) have identified reproduction and endocrine effects in F. heteroclitus as sensitive end-points that are responsive to endocrine-active contaminants in pulp mill effluents. These studies in killifish have led the way in determining the source(s) of contaminants within the mill process as well as confirming, for the purposes of environmental protection, an effective within-mill treatment process to remove the contaminants (Dubé and MacLatchy, 2001;Hewitt et al, 2002).…”
Section: Reproductive and Developmental Effectsmentioning
confidence: 99%